2019
DOI: 10.22603/ssrr.2017-0095
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of Intervertebral Disc Degeneration

Abstract: Abstract:Intervertebral disc degeneration is a well-known cause of disability, the result of which includes neck and back pain with associated mobility limitations. The purpose of this article is to provide an overview of the known molecular mechanisms through which intervertebral disc degeneration occurs as a result of complex interactions of exogenous and endogenous stressors. This review will focus on some of the identified molecular changes leading to the deterioration of the extracellular matrix of both t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 174 publications
0
46
0
2
Order By: Relevance
“…Jiang et al investigated autophagy and apoptosis as well as their interactions in NPCs under OS [ 9 ]. Other studies have determined that the expression of collagen type II and aggrecan was downregulated in hydroperoxide-induced NPCs [ 41 ]. However, these do not fully explain the decrease in NPCs and ECM degradation, as seen by the failure of drugs targeting these mechanisms to fully treat IVDD.…”
Section: Discussionmentioning
confidence: 99%
“…Jiang et al investigated autophagy and apoptosis as well as their interactions in NPCs under OS [ 9 ]. Other studies have determined that the expression of collagen type II and aggrecan was downregulated in hydroperoxide-induced NPCs [ 41 ]. However, these do not fully explain the decrease in NPCs and ECM degradation, as seen by the failure of drugs targeting these mechanisms to fully treat IVDD.…”
Section: Discussionmentioning
confidence: 99%
“…Intervertebral disc degeneration (IDD) is one of the most common causes of lower back pain and related disability [ 1 , 2 ]. Back pain is a common chronic medical problem worldwide, such that over 80% of adults are estimated to have suffered from back pain at some point in their lives [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, we have recently reported a significant association between the circulating levels of growth and differentiation factor 15 (GDF-15) and LBP disability in a large community-based sample [ 6 ]. Taking into account proposed involvement of inflammation in intervertebral disc (IVD) degeneration [ 7 , 8 , 9 , 10 ], the search for peripheral biomarkers has been conducted among pro-inflammatory factors that revealed, however, the inconsistent results [ 11 , 12 ]. Although controversial, other studies have suggested obesity as a risk factor in the development of LBP and other MSP syndromes [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%